Cyclic deformation behavior and life prediction of P92 steel welded joints under thermomechanical fatigue loadings. (June 2021) - Guo, Shen; Zhang, Wei; Yin, Peng; Ma, Tian-Hao; Wen, Jian-Bin; Zhang, Guo-Dong; Xue, Fei; Zhao, Yan-Fen; Zhou, Chang-Yu
Highlights: The fatigue life is sensitive to phase angle at relatively lower strain amplitude. The fracture location is strain amplitude and phase angle dependent. A modified energy-based life prediction model is proposed. Abstract: In the present work, thermomechanical fatigue behavior and life prediction of P92 steel welded joints under various mechanical strain amplitudes and phase angles are investigated. Results demonstrate that the welded joints exhibit significant cyclic softening during fatigue process and the thermomechanical fatigue life is strain amplitude and phase angle dependent. The decrease in strain amplitude and the increase in phase angle induce the increase in fatigue life. Fracture analysis indicates that the fracture position changes significantly with the strain amplitude and phase angle. Finally, a modified energy-based life prediction model is proposed by considering the effects of phase angle and mean stress.